Intracellular Accumulation of IFN-λ4 Induces ER Stress and Results in Anti-Cirrhotic but Pro-HCV Effects - Onabajo, Olusegun O.; Wang, Fang; Lee, Mei-Hsuan; Florez-Vargas, Oscar; Obajemu, Adeola; Tanikawa, Chizu; Vargas, Joselin M.; Liao, Shu-Fen; Song, Ci; Huang, Yu-Han; Shen, Chen-Yang; Banday, A. Rouf; et al. (Frontiers in Immunology, 2021)
IFNL3/IFNL4 polymorphisms are inversely associated with the risk of chronic hepatitis C virus (HCV) infection and cirrhosis, two major risk factors for developing hepatocellular carcinoma (HCC). To further explore these inverse associations and their molecular underpinnings, we analyzed IFNL3/IFNL4 polymorphisms represented by the IFNL4 genotype (presence of rs368234815-dG or rs12979860-T alleles) in HCV patients: 2969 from Japan and 2931 from Taiwan. IFNL4 genotype was associated with an increased risk of HCV-related HCC (OR=1.28, 95%CI=1.07-1.52, P=0.0058) in the general population of Japanese patients, but not in Taiwanese patients who achieved treatment-induced viral clearance. IFNL4 genotype was also associated with a decreased risk of cirrhosis (OR=0.66, 95%CI=0.46-0.93, P=0.018, in Taiwanese patients). We then engineered HepG2 cells to inducibly express IFN-λ4 in the presence or absence of interferon lambda receptor 1 (IFNLR1). Induction of IFN-λ4 resulted in its intracellular accumulation, mainly in lysosomes and late endosomes, and increased ER stress, leading to apoptosis and reduced proliferation. We identified the very-low-density lipoprotein receptor (VLDLR), which facilitates HCV entry into hepatocytes, as a transcript induced by IFN-λ4 but not IFN-λ3. Our results suggest that the molecular mechanisms underlying the anti-cirrhotic but pro-HCV associations observed for IFNL3/IFNL4 polymorphisms are, at least in part, contributed by intracellular accumulation of IFN-λ4 causing ER stress in hepatic cells.